Nurses’ professional performance in the organs donation and procurement process in eligible donors - Nayresson de Sousa Carvalho, Jordele de Sousa, Laurimary Caminha Veloso, Karine de Magalhães Nogueira Ataide (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/2238-7234.8123-29